DAMPAK RATIFIKASI PROTOKOL KYOTO TERHADAP KEBIJAKAN PEMERINTAH INDONESIA DALAM MENJAGA KELESTARIAN EKOSISTEM HUTAN DI PROVINSI RIAU TAHUN 2004-2014 - Cindy Claudia; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes the impact of ratification Kyoto Protocoll to support the policy of Indonesia Government in maintanance of foresst ecology in Riau Province in 2004-2014. Kyoto Protocoll are one of the international conventions that focus to keep a environment problems.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the role of international organization for migration in antisipated human trafficking in Indonesia. The theories applied in this research are realism perspective with decision making theory by William D Coplin.The conclusion of this research about impact of ratification Kyoto Protocoll to support the policy of Indonesia Government in maintanance of foresst ecology in Riau Province are ratification some regulations to reduction emition from deforestation and forest degradation. The regulations are constitution number 17 in 2004 about ratifications of Kyoto Protocol, ratifications of Forest Minister regulations number 68/Menhut-II/2008 about reduction emition from deforestation.Key words: impact, policy, environment and kyoto protocoll